q+3=9

To remove the radical on the left side of the equation, square both sides of the equation.

q+32=92

Multiply the exponents in ((q+3)12)2.

Apply the power rule and multiply exponents, (am)n=amn.

(q+3)12⋅2=92

Cancel the common factor of 2.

Cancel the common factor.

(q+3)12⋅2=92

Rewrite the expression.

(q+3)1=92

(q+3)1=92

(q+3)1=92

Simplify.

q+3=92

Raise 9 to the power of 2.

q+3=81

q+3=81

Subtract 3 from both sides of the equation.

q=81-3

Subtract 3 from 81.

q=78

q=78

Solve using the Square Root Property square root of q+3=9